Analysis Of Factors Affecting Adoption Of Financial Technology Application - Chalimatuz Sa'diyah (Universitas Muhammadiyah Sorong, 2021)
Financial technology has been an invaluable instructional material in the global science and technology trend and is the target of new technology applications of great business potential. This study aims to analyze the influence of brand and service trust, perceived usefulness, perceived ease of use on behaviour intention through attitude on fintech users. This research method uses purposive sampling method with the criteria of entrepreneurs using financial technology and located in Malang city. The number of samples used in this study was 160 respondents. Data interpretation using the Smart PLS3 system for analysis. The results showed that brand and service trust affects attitude. Perceived usefulness affects attitude. Perceived ease of use affects attitude. Attitude affects to Behavior Intention. Attitude variable can mediate the influence of Brand and Service Trust, Perceived Usefulness and Perceived Ease of Use on Behavior Intention. The Sobel test results show that the bigger indirect effect is the influence of Brand and Service Trust on Behavior Intention through Attitude.